2019
DOI: 10.15625/2525-2518/57/5/13661
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterizations of plasticized PMMA/PVC/Mg(ClO<sub>4</sub>)<sub>2</sub> electrolytes

Abstract: Electrolyte films based on poly(methyl methacrylate) (PMMA), poly(vinyl chloride) (PVC) were prepared by using casting method with the addition 100 wt.% to 240 wt.% of dioctyl phthalate (DOP), propylene carbonate (PC) as plasticizers and Mg(ClO4)2 as an electrolytic salt. The Fourier infrared spectra (FTIR), tensile, electrical properties, surface morphology of electrolyte films were investigated. The FTIR spectra of plasticized PMMA/PVC blends indicated that there were secondary interactions between plasticiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…In our previous study, we have reported the mechanical and dielectrical properties of GPBEs doped with Mg(ClO 4 ) 2 salt [21]. It was found that plasticizers are very important to improve the ionic conductivity of the GPBEs.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, we have reported the mechanical and dielectrical properties of GPBEs doped with Mg(ClO 4 ) 2 salt [21]. It was found that plasticizers are very important to improve the ionic conductivity of the GPBEs.…”
Section: Introductionmentioning
confidence: 99%